2003
DOI: 10.1073/pnas.0631825100
|View full text |Cite
|
Sign up to set email alerts
|

Instability of GGL domain-containing RGS proteins in mice lacking the G protein β-subunit Gβ5

Abstract: RGS (regulator of G protein signaling) proteins containing the G protein ␥-like (GGL) domain (RGS6, RGS7, RGS9, and RGS11) interact with the fifth member of the G protein ␤-subunit family, G␤5. This interaction is necessary for the stability of both the RGS protein and for G␤5. Consistent with this notion, we have found that elevation of RGS9-1 mRNA levels by transgene expression does not increase RGS9-1 protein level in the retina, suggesting that G␤5 levels may be limiting. To examine further the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
212
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(227 citation statements)
references
References 38 publications
15
212
0
Order By: Relevance
“…The functional knock-out of all four R7 proteins, which takes place in the G␤5 knock-out mice, leads to multiple health problems, low body weight, and a high mortality rate (24). A less severe but also well identifiable phenotype was documented in the RGS9 knock-out mice.…”
Section: Novel Interacting Partner Of R7 Rgs Proteins 5135mentioning
confidence: 96%
“…The functional knock-out of all four R7 proteins, which takes place in the G␤5 knock-out mice, leads to multiple health problems, low body weight, and a high mortality rate (24). A less severe but also well identifiable phenotype was documented in the RGS9 knock-out mice.…”
Section: Novel Interacting Partner Of R7 Rgs Proteins 5135mentioning
confidence: 96%
“…Thus, for example, ablation of G␥ subunit expression destabilizes uncomplexed G␤ (31). Furthermore, RGS proteins containing the G protein ␥-like domain (RGS6, RGS7, RGS9, and RGS11) are G␤ 5 binding partners; they are destabilized and degraded in mice lacking G␤ 5 , and reciprocally, G␤ 5 protein is degraded in the absence of a suitable interacting subunit (32,33). To examine the stability of G␣ and G␥ subunits as a function of G␤ suppression, we performed quantitative RT-PCR and Western blotting.…”
Section: Expression Of G␥ Subunits Was Down-regulated In the Cells Lamentioning
confidence: 99%
“…These studies revealed that Gb5 and R7BP knockout mice have dramatically diminished levels of RGS9-2 protein (Chen et al, 2003;Anderson et al, 2009), that loss of R7BP affects RGS9-2 localization and striatal signaling (Anderson et al, 2009), and that pharmacological manipulations, or changes in neuronal excitability affect the composition of R7 complexes in the striatum (Anderson et al, 2009;Psifogeorgou et al, 2011). Recent evidence from genetic mouse models suggests that R7BP has a key role in regulation of GPCR responses in the basal ganglia, via interactions with RGS9-2 and RGS7.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the R7 family share several domains and form constitutive complexes with the type 5 G protein b subunit (Gb5) (Sondek and Siderovski, 2001;Cheever et al, 2008). The R7-Gb5 association is essential for the protein's stability and function (He et al, 2000;Chen et al, 2003). R7 proteins also share a DEP domain (Martemyanov et al, 2003;Ballon et al, 2006), which is required for their interaction with the adaptor molecules R9AP in the retina (Hu and Wensel, 2002) and R7 family binding protein (R7BP) in the brain (Martemyanov et al, 2005).…”
Section: Introductionmentioning
confidence: 99%